Profil Miskonsepsi Siswa Kelas X Smkn 4 Mataram pada Materi Pokok Suhu, Kalor, dan Perpindahan Kalor - P. Ayu Suci Lestari; Satutik Rahayu; Hikmawati Hikmawati (Department of Physics Education, Universitas Mataram, 2015)
This research aimed to describe the students misconception profile for grade X SMKN 4 Mataram on the subject matter of Temperature, Heat, and Heat Transfer. This research is descriptive with case study design. The population in this research were all students of grade X SMK 4 Mataram which amounts to 424 people. The sampling technique used was purposive sampling, so that the sample in this research were all students of grade X SMK 4 Mataram except for class X of Office Administration 1 (X APK 1) and X of Office Administration 2 (X APK 2) which amounts to 333 people, because only both ofÃÂ this grade that do not get science subjects. Data were obtained from the test instrument identification shaped misconceptions reasoning multiple choice with an open reasoning and the analyzed using descriptive statistics which have previously been validated by one person subject teacher Science grade X and two person physical education lecturer. Based on this research, it was found that the students of grade X SMK 4 Mataram academic year 2014/2015 have misconceptions identified by the average percentage of misconceptions on the concept of temperatures by 11.53%, on the concept of heat by 16.44%, on the concept of expansion by 8.61%, and on the concept of heat transfer by 15.22%, so it can be concluded that the misconceptions experienced by the students of grade X SMK 4 Mataram in Akademic Year 2014/2015.